Association Between Firearm Purchasing in Response to the COVID-19 Pandemic and Symptoms of Anxiety, Depression, and Stress, August 2021 - Amira A. Roess, PhD; Laura F. Henderson, MPH; Leah M. Adams, PhD; Keith D. Renshaw, PhD (AJPM Focus, 2024)
Introduction: Firearm sales and firearm-related injuries and deaths increased during the pandemic. Little is known about motivations for firearm purchasing in response to the COVID-19 pandemic and the mental health status of first-time purchasers. The purpose of this study was to estimate the association between firearm purchasing in response to the COVID-19 pandemic and anxiety symptoms, depressive symptoms, and stress. Methods: The authors analyzed data from a survey that approximated a nationally representative sample of American adults (N=3,528) who either did not own firearms (n=2,327) or purchased firearms for the first time in response to the pandemic (n=240). Self-reported stress, depressive symptoms, and anxiety symptoms were determined using standardized self-assessment questionnaires (Perceived Stress Scale, Patient Health Questionnaire, and Depression Anxiety Stress Scale, respectively). Using multivariable logistic regression, the association between firearm purchasing and each mental health measure were assessed after controlling for demographics and other determinants. Results: In each model, first-time firearm owners were more likely to be younger, live in urban areas, believe the government does too much for its citizens, stay home, stock up on items, and keep their children at home. First-time owners had significantly higher odds of anxiety and depressive symptoms than non-owners (AOR=1.05; 95% CI=1.04, 1.07 and AOR=1.15; 95% CI=1.04, 1.26, respectively). Conclusions: First-time firearm purchasers report higher depressive and anxiety symptoms than non-owners, suggesting that there may be a risk of suicide and other related firearm violence.